Magnetic Resonance Imaging Follow-up Study on Two Cases of Lumbar intervertebral Disc Sequestration Patients Treated with Oriental Medicine Treatment - Ki-Su Lee; Kwon-Eui Hong (Korean Pharmacopuncture Institute, 2011)
Objectives: The purpose of this study is to report the image changes of two cases of Lumbar intervertebral Disc Sequestration after oriental medical treatment. Methods: We examined 2 patients with Lumbar intervertebral Disc Sequestration who showed changes on MRI images before/after the treatment. And we assessed clinical symptoms by using numeric rating scale(NRS) and straight leg raising test(SLRT). Results & Conclusions : In this study, the first MRI examination of Lumbar intervertebral Disc Sequestration patients was performed at the first visit and re-examination of MRI was done after treatment. In each case, the size of the disc sequestration was considerably reduced in MRI image. And both patients represented effective improvment in NRS score and SLRT test angle.